Pengaruh Brand Ambassador Dan Endorsement Terhadap Keputusan Pembelian: Penelitian - Anisa Putri Br Lubis; Sumiati Pardede; Putri Paskah Patricia Sipahutar; Esra Srimingsi Simanjuntak; Roza Thohiri (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
The influence of brand ambassadors and endorsements on consumer purchasing decisions is very large. This study aims to see the influence of brand ambassadors and endorsements on consumer purchasing decisions. This study uses a quantitative method with a survey of 100 respondents of social media users. Then analyzed with multiple linear regression to see the influence of the variables studied. The results of the study indicate that the Endorsement and Brand Ambassador variables have a positive but very weak relationship to consumer purchasing decisions. The correlation coefficient of 0.165 and the determination coefficient (R Square) of only 2.7% indicate that the two variables are only able to explain a small part of the variation in consumer purchasing decisions, while most (97.3%) are influenced by other factors outside this research model.